1998
DOI: 10.1046/j.1420-9101.1998.11040439.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the colonization of Madeira and the Canary Islands by Drosophila subobscura through the study of the rp49 gene region

Abstract: Nucleotide variation at the nuclear ribosomal protein 49 (rp49) gene region has been analysed by fine restriction mapping in a sample of 47 lines from a population from Madeira. Five restriction-site (out of 37 sites scored) and 3 length polymorphisms have been detected, resulting in 14 different haplotypes. This population shows less variation than both continental and Canary Island populations. The population from Madeira shows some differentiation from mainland populations, which does not favor the idea of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Some studies of colonization patterns in other organisms in the Canary Islands have shown stepping-stone models of dispersal from older to progressively younger islands, for example, the tenebrionid beetles Pimelia and Hegeter are both essentially compatible with a stepping-stone model, with a probable back colonization from Tenerife to Gran Canaria in Pimelia (Juan et al, 1995(Juan et al, , 1996. The curculionid beetle Brachyderes rugatus and Drosophila subobscura are both absent in the eastern Canary Islands, but show a pattern of sequential colonization from older to younger islands in the west (Emerson et al, 2000a;Khadem et al, 1998;Pinto et al, 1997). In addition to simple stepping-stone models, more complex patterns of island colonization have also emerged in a range of organisms.…”
Section: Patterns Of Island Colonizationmentioning
confidence: 99%
“…Some studies of colonization patterns in other organisms in the Canary Islands have shown stepping-stone models of dispersal from older to progressively younger islands, for example, the tenebrionid beetles Pimelia and Hegeter are both essentially compatible with a stepping-stone model, with a probable back colonization from Tenerife to Gran Canaria in Pimelia (Juan et al, 1995(Juan et al, , 1996. The curculionid beetle Brachyderes rugatus and Drosophila subobscura are both absent in the eastern Canary Islands, but show a pattern of sequential colonization from older to younger islands in the west (Emerson et al, 2000a;Khadem et al, 1998;Pinto et al, 1997). In addition to simple stepping-stone models, more complex patterns of island colonization have also emerged in a range of organisms.…”
Section: Patterns Of Island Colonizationmentioning
confidence: 99%
“…O 3+4+8 in North‐western Africa and O 3+4+7 in the Atlantic coast of the Iberian peninsula) does not seem to favour the hypothesis of recent migration from the continent. Otherwise, selection against the establishment of these other arrangements in the islands should be very strong given their high frequency in those continental populations (see Khadem et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, O 3+4 lines from these locations are not genetically differentiated for that region. Some differentiation had been, however, detected in a previous restriction‐map survey (Khadem et al ., 1998). The discrepancy between the results of these studies might be partly due to the relatively low number of nucleotides sampled in the previous study and therefore to the high stochastic variance associated with nucleotide variation estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations